2021
DOI: 10.1002/bies.202100124
|View full text |Cite
|
Sign up to set email alerts
|

Collective cell migration driven by filopodia—New insights from the social behavior of myotubes

Abstract: Collective migration is a key process that is critical during development, as well as in physiological and pathophysiological processes including tissue repair, wound healing and cancer. Studies in genetic model organisms have made important contributions to our current understanding of the mechanisms that shape cells into different tissues during morphogenesis. Recent advances in high-resolution and live-cell-imaging techniques provided new insights into the social behavior of cells based on careful visual ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 126 publications
(189 reference statements)
0
10
0
Order By: Relevance
“…It is well-known that the newly formed filopodia as a key factor is associated with cell migration and metastasis [ 32 ]. Generally, field-induced responses involving actin cytoskeleton reassembly will inevitably result in morphological reorganization, which can be directly investigated by the percentage of actin polymerization (ratio of cells with actin reassembly to total number of cells) and the surface area of cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that the newly formed filopodia as a key factor is associated with cell migration and metastasis [ 32 ]. Generally, field-induced responses involving actin cytoskeleton reassembly will inevitably result in morphological reorganization, which can be directly investigated by the percentage of actin polymerization (ratio of cells with actin reassembly to total number of cells) and the surface area of cells.…”
Section: Resultsmentioning
confidence: 99%
“…[46] In short, contact inhibition of migration is the mechanism by which a cell stops or changes the direction of migration when it collides with another cell, [47][48][49][50] while contact stimulation of migration is the mechanism by which one cell contacts another cell to activate cell migration. [51][52][53] From Figure 6b, it was found that for the undifferentiated cells on the 22 kPa hydrogel, one cell encountering another cell would change the direction of migration (contact inhibition of migration). However, for undifferentiated cells at 22 kPa with AS, one cell contacting another cell could activate the cell migration (contact stimulation of migration).…”
Section: Synergistic Effect Of Matrix and Fss On Cell Migrationmentioning
confidence: 99%
“…Based on widely reported cell migration studies, it was confirmed that the fundamental mechanics of single-cell migration may be applied to collective movement, as well. During group migration, the cells stay attached throughout the process, allowing cell–cell junctions to remain intact during movement. ,,, Collective migratory behaviors occur in response to a variety of environmental limitations, which result in a range of morphological characteristics. They include the presence of mesenchymal leader cells that are highly motile, cryptic lamellipodia development by cells placed a few rows behind the leading front and the formation of small groups of follower cells that are directed by the leader ones .…”
Section: Cell Migrationmentioning
confidence: 99%
“…They are in charge of controlling the direction of movement, moreover they support persistence of migratory cells via increasing cell−matrix adhesion at the leading edge. 38 2.2. Collective Cell Migration.…”
Section: Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation